The concept of ocular inserts as drug delivery systems: An overview - Karthikeyan, Deivasigamani; Bhowmick, Mithun; Pandey, Vijay Prakesh; Nandhakumar, Jothivel; Sengottuvelu, Singaravel; Sonkar, Sandeep; Sivakumar, Thangavel (Asian Journal of Pharmaceutics (AJP), 2014)
Ocular diseases require localized administration of drugs to the tissues around the ocular cavity. The existing ocular drug delivery systems are fairly primitive and inefficient. However, the design of ocular system is undergoing gradual transition from an empirical to rational basis. In the recent years, there has been explosion of interest in the polymer based delivery devices. Utilization of the principles of controlled release as embodied by ocular inserts offers an attractive approach to the problem of prolonging pre-corneal drug residence times. In the present update, the authors discuss the basic concept of ocular inserts as drug delivery system and examine the few inserts, which are available in the market or are being developed by pharmaceutical companies for drug delivery.The article discusses soluble ocular drug insert (SODI), Ocusert, Collagen Shields, Ocufit, Minidisc and new ophthalmic delivery system (NODS) with special attention to biological/clinical performances, and potential for future applications and developments.